PERSPECTIVE ON ICT IN TEACHING AND LEARNING LISTENING & SPEAKING IN THE 21ST CENTURY: BEYOND CLASSROOM WALL - Gumawang Jati (TLEMC (Teaching and Learning English in Multicultural Contexts), 2017)
Rapid evolution of communication technologies has changed language pedagogy and language use, enabling new ways of learning, new forms of authorship, and new ways to teach beyond cognitive, classroom wall and curriculum. The first section of this paper identifies and discusses 3 major issues related to ICT: behaviorism, cognitive approach, and integrative ICT. Computer software and Apps for teaching and learning speaking listening are discussed in term of their effectiveness. The second section discusses the development of ICT (Internet Communication Technology) in the 21st century and its common practice done by English teachers, especially in teaching listening and speaking. The third section discusses the implication for teaching and learning and what teachers and students can do beyond the classroom wall